An ACO-based algorithm for parameter optimization of support vector machines - Zhang, XiaoLi; Chen, XueFeng; He, ZhengJia (Expert systems with applications, 2010)
One of the significant research problems in support vector machines (SVM) is the selection of optimal parameters that can establish an efficient SVM so as to attain desired output with an acceptable level of accuracy. The present study adopts ant colony optimization (ACO) algorithm to develop a novel ACO-SVM model to solve this problem. The proposed algorithm is applied on some real world benchmark datasets to validate the feasibility and efficiency, which shows that the new ACO-SVM model can yield promising results.